Environmental Analysis of the COVID-19 Climate - Elsa Yuniarti; Linda Rosalina; Vauzia Vauzia; Erna Juita; Syovia Amimi; Sari Ramadhani (Postgraduate, University of Mataram, 2023)
The most-high matter of COVID-19 in West Sumatera Province was found in Padang City. Some researchers argue that the environment greatly influences contagion of COVID-19. This research aims to anatomize the COVID-19 climate environment in Padang City in the period March 16th 2020 – May 20th 2022. The study used secondary data in the form of COVID-19 surveillance data, namely the number of patients who were confirmed positive for COVID-19 from the Padang City Health Office and the climate from the Meteorology and Climatology Agency of Padang City. Weather elements include maximum temperature (°C), minimum temperature (°C), average temperature (°C), humadity (%), and rainfall (mm). Data analysis used pearson correlation. The result of the study indicated that minimum temperature and rainfall had a significant relationship to positive matters of COVID-19 in Padang City which were marked with p-values of 0.004 and 0.